(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Blockchain is one of the most recent organization based advancements, which will fundamentally affect most businesses including the travel industry. Despite the fact that blockchain innovation is at the outset phase of improvement, apparatuses like digital currencies, keen agreements, and Decentralized Applications have started to impact the travel industry exchanges. This paper makes an endeavor to feature the critical attributes of blockchain innovation related to the Smart city/the travel industry structure while making suggestions of how the innovation would develop and impact the business. Significant issues identified with the innovation just as difficulties are likewise talked about, including a few misinterpretations